2005
DOI: 10.1002/ep.10078
|View full text |Cite
|
Sign up to set email alerts
|

A life cycle assessment of mechanical and feedstock recycling options for management of plastic packaging wastes

Abstract: Life cycle assessment (LCA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(189 citation statements)
references
References 28 publications
8
165
1
1
Order By: Relevance
“…Another study conducted by Arena et al [5] defined through the analytical comparison between the six scenarios showed that the recycling option always environmentally preferable. Another study from Perugini et al [6] confirmed that recycling scenarios are always preferable to those of non-recycling. Thus, recycling is one appropriate technology which could be considered to avoid greater impact to environment.…”
Section: Life Cycle Assessment Of Plastic Waste Management Systemmentioning
confidence: 93%
“…Another study conducted by Arena et al [5] defined through the analytical comparison between the six scenarios showed that the recycling option always environmentally preferable. Another study from Perugini et al [6] confirmed that recycling scenarios are always preferable to those of non-recycling. Thus, recycling is one appropriate technology which could be considered to avoid greater impact to environment.…”
Section: Life Cycle Assessment Of Plastic Waste Management Systemmentioning
confidence: 93%
“…Since there is no PET recycling process in the GaBi ® Database, inventory data from two different PET recycling processes found in the literature were used [36,37]. Data from Arena et al [37] were used in the study, and sensitivity analysis was performed with Perugini et al [36] data in order to analyse their influence on the final results. Tables S1 and S2 in Supplementary Material (SM) include the data that was used.…”
Section: Assumptionsmentioning
confidence: 99%
“…LCAs usually attempt to take every stage of product life cycle into account (Perugini et al, 2005) from raw material acquisition to final disposal.…”
Section: Lca Frameworkmentioning
confidence: 99%
“…Interestingly, two LCAs compared incineration and an advanced thermal treatment technology pyrolysis (Perugini et al, 2005, Azapagic, 2007. Although different wastes were modelled, both studies indicated that pyrolysis gives more favourable environmental profile than incineration for MSW treatment in terms of energy consumption/recovery.…”
Section: Lca Of Incinerationmentioning
confidence: 99%
See 1 more Smart Citation